An Experimenter's Guide to Glioblastoma Invasion Pathways. Issue 9 (September 2018) - de Gooijer, Mark C.; Guillén Navarro, Miriam; Bernards, Rene; Wurdinger, Thomas; van Tellingen, Olaf
Abstract : Glioblastoma is a highly aggressive brain tumor that is characterized by its unparalleled invasiveness. Invasive glioblastoma cells not only escape surgery and focal therapies but also are more resistant to current radio- and chemo-therapeutic approaches. Thus, any curative therapy for this deadly disease likely should include treatment strategies that interfere with glioblastoma invasiveness. Understanding glioblastoma invasion mechanisms is therefore critical. We discuss the strengths and weaknesses of various glioblastoma invasion models and conclude that robust experimental evidence has been obtained for a pro-invasive role of Ephrin receptors, Rho GTPases, and casein kinase 2 (CK2). Extensive interplay occurs between these proteins, suggesting the existence of a glioblastoma invasion signaling network that comprises several targets for therapy. Highlights: Glioblastoma (GBM) is a highly aggressive brain tumor that is characterized by an unparalleled invasion capacity. GBM cells invade the brain via the brain parenchyma, the perivascular space, white matter tracts, and the leptomeningeal space. GBM invasion signaling is dependent on the brain microenvironment, including extracellular matrix composition. A pro-invasive GBM signaling network is emerging from literature revolving around Ephrin receptors, Rho GTPases, and casein kinase 2 that offers several druggable targets.